45 Threshold dose for focal liver reaction. (December 2018) - Spiazzi, L.; Toraci, C.; Frassine, F.; Borghetti, P.; Altabella, L.; Vitali, P.; Polonini, A.; Moretti, R
Abstract : Purpose: Patient who underwent liver stereotactic body radiation therapy (SBRT) show a signal intensity alteration in follow-up imaging known as focal liver reaction (FLR). This study aims at evaluating dose threshold for FLR after SBRT. Methods: 22 patients (13 metastasis, 9 hepatocellular carcinomas [hcc]) underwent SBRT with 48 or 60 Gy in 3 fractions. After therapy patients had, according to clinical protocols, follow-up imaging studies (12 CT and 32 MRI) at 3, 6, 9, 12, 18, 24 and 30 months. For each follow-up the region of signal alteration, if present, was classified as FLR, residual or recurrent disease, and contoured. In case of FLR, the planning images were registered to the follow up using deformable registration, and planning dose was mapped to the follow up applying the registration matrix. The isodose that better fits the FLR ( dose threshold ) was found, and the conformality index between dose threshold and FLR computed. The figure shows the dose threshold as a function of cancer type and follow up time. Results: Threshold dose is higher for metastasis than for hcc (8 Gy at 3–6 months, 12 Gy at 9–12 months), and shows an increase up to 9 months followed by a decrease at 12 month. Cases at 18 or more months are too few or broad to be significant. The table shows threshold doses with their uncertainties – cases with just one samples are excluded. Conclusions: hcc's show FLR for lower doses, which can be justified by pre-existing cirrhosis. Since higher isodoses are embedded in lower ones, follow-up lesion size has an inverse correlation with dose threshold; therefore, there is a decrease of the lesion in the first 9 months followed by an increase 3 months later. Threshold doses are consistent with literature data.